Training of public health workforce at the National School of Public Health: meeting Africa's needs - Kebogile Mokwena; Mathilda Mokgatle-Nthabu; Sphiwe Madiba; Helen Lewis; Busi Ntuli-Ngcobo
PROBLEM: The inadequate number of trained public health personnel in Africa remains a challenge. In sub-Saharan Africa, the estimated workforce of public health practitioners is 1.3% of the world's health workforce addressing 25% of the world's burden of disease. APPROACH: To address this gap, the National School of Public Health at the then Medical University of Southern Africa created an innovative approach using distance learning components to deliver its public health programmes. Compulsory classroom teaching is limited to four two-week blocks. RELEVABT CHANGES: Combining mainly online components with traditional classroom curricula reduced limitations caused by geographical distances. At the same time, the curriculum was structured to contextualize continental health issues in both course work and research specific to students' needs. LESSONS LEARNED: The approach used by the National School of Public Health allows for a steady increase in the number of public health personnel in Africa. Because of the flexible e-learning components and African-specific research projects, graduates from 16 African countries could avail of this programme. An evaluation showed that such programmes need to constantly motivate participants to reduce student dropout rates and computer literacy needs to be a pre-requisite for entry into the programme. Short certificate courses in relevant public health areas would be beneficial in the African context. This programme could be replicated in other regions of the continent.